The World Turned Upside Down: America, China, and the Struggle for Global Leadership - Tooba Ghaffar (CISS Insight Journal, 2021)
The crux of the book can be summarized in one sentence: the US made a blunder supporting China’s membership to the World Trade Organization (WTO). It was done in the hope that China will act as a responsible stakeholder in the global rule-based system. But it was not to be; according to the author, this was not in line with China’s great dreams. China’s dream is to make China great again and to achieve greatness, it would employ all possible means even evading or maneuvering around the WTO’s policies whenever it is needed.Prestowitz argues that historically whoever tried to conquer China, for instance Mongols and the Manchus, were absorbed by the Chinese people and culture. Even after humiliating China in the Opium Wars, Britain was not able to conquer China like it did countries in other regions. Chinese have a legacy of dominating the foreigners instead of being dominated. The author elaborates how Americans generally got overwhelmed by the Chinese culture, and intellect of its leadership with certain examples. In 1972, Henry Kissinger engaged with the Chinese leaders for the first time, with ambitious plans of convincing them to release all the Americans in the Chinese custody, make them help in persuading North Vietnam to accept a peace deal and agree to an official visit by President Nixon to the Chinese Mainland. Kissinger, overawed in the presence of Chinese leadership, ended up making concessions himself and could only convince Zhou Enlai and Mao Zedong to accept an official visit by the American President.